High Arsenic Stress Enhances the Expression of Virulence Factor Genes and Pathogens in Paddy Soils via Network Restructuring and Potential Horizontal Gene Transfer - Zi-Teng Liu; Jia-Qi Li; Xin-Di Zhao; Zi-Yu Gao; Si-Yu Zhang (Environment & Health, 2026)
Abstract Virulence factor genes (VFGs) in soil microbiomes pose potential health risks, yet how environmental stressors drive their enrichment remains poorly understood. We integrated metagenomic and metatranscriptomic analyses with a time series microcosm experiment (6 h to 60 days) to investigate VFG responses to arsenic (As) stress in paddy soils. High-As stress (150 mg kg–1) reduced overall microbial alpha diversity at the DNA level but paradoxically drove co-occurrence networks of potential pathogens toward a highly interconnected architecture dominated by positive associations (98.50%), with global transitivity increasing to 0.874. This restructuring was accompanied by significant enrichment of VFGs, particularly those involved in adherence, motility, and biofilm formation, with As(III) identified as the primary driver of VFG expression. VFGs showed strong transcriptional coupling with mobile genetic elements, and 35 high-quality metagenome-assembled genomes carrying VFG-MGE pairs provided direct genomic evidence of horizontal transfer potential. Notably, VFG upregulation reflected a community-level stress tolerance strategy rather than a direct shift toward pathogenicity, yet the unintended consequence was sustained time-dependent enrichment of opportunistic pathogens, including ESKAPE pathogens, with 53 potential pathogens transcriptionally active by day 60. Our findings establish that As-contaminated paddy soils serve as hidden reservoirs for VFGs and opportunistic pathogens, with implications for food safety and One Health risk assessment.